VD_FINDINFO Pron / 2013 / 128 vom 28. Mai 2013 - VD Tribunal cantonal (2013)
CURATEUR, CHOIXEN GÉNÉRAL, PROCÈS DEVENU SANS OBJET, RECONSIDÉRATION | 400 al. 1 CC, 400 CC, 450 CC, 450d al. 2 CC, 242 CPC (CH)